Utilization of Fungal-Derived Chitosan from Flammulina Filiformis (Enoki Mushroom) and Pleurotus Ostreatus (Oyster Mushroom) as a Natural Coagulant in Wastewater Treatment - Saiful, Nur Afiqah Sahira; Nor Faizah Razali (Progress in Engineering Application and Technology, 2026)
This research works on the use of chitosan derived from fungi, specifically enoki mushrooms (Flammulina filiformis) and oyster mushrooms (Pleurotus ostreatus), as a natural coagulant in treating wastewater. The purpose of this research is to derive chitosan from enoki and oyster mushrooms, determine its physicochemical property, and test its coagulation efficacy as an alternative to conventional alum. Chitosan is derived through various steps, including deproteinization, treatment with acid, decolorization, and deacetylation. The derived chitosan was analyzed using Fourier Transform Infrared Spectroscopy (FTIR), Zeta potential, rheology test, and yield test. Coagulation efficacy was determined using jar test experiments at differing pH levels, wherein turbidity levels served as indicators. The findings show that chitosan derived from enoki mushrooms had chitin yields of 6.50%, having much higher positive surface charges, with zeta potential measurements above +70 mV, portraying high electrostatic attraction forces. Zeta potential measurements presented much smaller values, merely +50 mV. Rheological tests revealed that all samples had high shear rates, reducing viscosity values ranging from 100 Pa.s to 10-1-10-3 Pa.s when increased. Jar test experiments revealed chitosan derived from fungi having high turbidity removal rates, about 90-96%, almost comparable to those derived using alums. In general, this research concludes that chitosan derived from enoki mushrooms possessed high surface charges, superior coagulation rates, and is thus viable and promising as sustainable, eco-friendly natural coagulants.